CONTROL OF CARBON (II) OXIDE FROM THE COMPOSITION OF GASES CREATION OF A SEMICONDUCTOR SENSOR FOR - Eshkobilova M.E.; Sidiqova X.G‘.; Smanova Z.А.; Аbduraxmanov E., (FAN VA TA'LIM INTEGRATSIYASI (INTEGRATION OF SCIENCE AND EDUCATION), 2024)
As a result of the experiments carried out in this work, selective semiconductor sensors were developed; these sensors provide rapid detection of CO from the composition of atmospheric air and exhaust gases of technological processes. The developed semiconductor sensors are not inferior to the existing foreign analogues in terms of accuracy and reproducibility of the results obtained, while maintaining the advantage of portability, ease of manufacture and operation. These sensors detect Carbon(II) monoxide over a wide range of concentrations and are recommended for use in the analysis of complex mixtures.